2023
DOI: 10.1111/obr.13574
|View full text |Cite
|
Sign up to set email alerts
|

GLP‐1 analogs and regional adiposity: A systematic review and meta‐analysis

Ioannis Akoumianakis,
Anastasios Zagaliotis,
Maria Konstantaraki
et al.

Abstract: Background: Glucagon-like peptide 1 (GLP-1) analogs regulate body weight and liver steatosis. Different body adipose tissue (AT) depots exhibit biological variability.Accordingly, GLP-1 analog effects on AT distribution are unclear.Objectives: To investigate GLP1-analog effects on adiposity distribution.Search methods: PubMed, Cochrane, and Scopus databases were screened for eligible randomized human trials. Pre-defined endpoints included visceral AT (VAT), subcutaneous AT (SAT), total AT (TAT), epicardial AT … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 89 publications
0
3
0
Order By: Relevance
“…Glucagon-like peptide-1 (GLP-1) agonists have the potential to lessen the severity of NAFPD, by modulating the ER stress pathway and the subsequent signaling of apoptosis in mice models, and to alter regional adiposity in humans. 121,122 Moreover, the synergistic activity of sitagliptin, a dipeptidyl peptidase (DPP) 4 inhibitor which prolongs the action of GLP-1 and insulin secretion from pancreatic β-cells, with telmisartan, which modulates inflammatory responses and improves endothelial function, exhibits remarkable efficacy in effectively managing the progression of NAFPD in mice. 123 Based on evidence from experimental models, GLP-1 agonists consist the most promising class of drugs for the treatment of NAFPD122 and prospective trials are needed to verify these data.…”
Section: Treatment Of Nafpdmentioning
confidence: 99%
“…Glucagon-like peptide-1 (GLP-1) agonists have the potential to lessen the severity of NAFPD, by modulating the ER stress pathway and the subsequent signaling of apoptosis in mice models, and to alter regional adiposity in humans. 121,122 Moreover, the synergistic activity of sitagliptin, a dipeptidyl peptidase (DPP) 4 inhibitor which prolongs the action of GLP-1 and insulin secretion from pancreatic β-cells, with telmisartan, which modulates inflammatory responses and improves endothelial function, exhibits remarkable efficacy in effectively managing the progression of NAFPD in mice. 123 Based on evidence from experimental models, GLP-1 agonists consist the most promising class of drugs for the treatment of NAFPD122 and prospective trials are needed to verify these data.…”
Section: Treatment Of Nafpdmentioning
confidence: 99%
“…Evidence supports that a decrease in visceral fat tissue can ameliorate obesity-related metabolic complications [1,6]. Previous systematic reviews found that GLP1-RAs significantly reduced adiposity (i.e., visceral, subcutaneous, and epicardial fat) [13][14][15]. However, these systematic reviews did not simultaneously compare individual GLP1-RAs therapy or different dosage regimens among overweight or obese persons with or without type 2 diabetes [13][14][15].…”
Section: Plos Onementioning
confidence: 99%
“…However, there are several limitations regarding the currently available systematic review and meta-analysis of GLP1-RAs among adult overweight or obese persons. These include the following: (i) most of existing reviews focused mainly on glycemic control and weight reduction, in which not comprehensive to body composition and anthropometric indices outcome [ 12 , 16 , 17 ]; (ii) the effect estimates are based on the synthesis of a combination of medication class therapy (pairwise meta-analysis) rather than comparison among individual GLP1-RAs therapy [ 13 15 ]; and (iii) studies being based on mixed populations or focused on particular population (i.e., nonalcoholic fatty liver disease or polycystic ovary syndrome) [ 8 , 9 , 11 , 12 , 15 ]. In this regard, no systematic review has compared individual GLP1-RAs therapy or different dosage regimens among overweight or obese persons with or without type 2 diabetes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation